Totally Ultrasound-Guided Supine Mini-PCNL Without Ureteral Catheter in Hydronephrotic Kidney; A Matched-Pair Analysis - çanakcı, Cengiz; özkaptan, Orkunt; Dinçer, Erdinç; Can, Utku; çağlar, Kubilay Can; Türkyılmaz, Oğuz (Urology Journal, 2026)
Purpose: To investigate the safety and efficacy of supine percutaneous nephrolithotomy performed completely under ultrasound guidance without fluoroscopy and ureteral catheterization in kidneys with hydronephrosis. Materials and Methods: This retrospective study analyzed the data of 30 patients (Group 1) with kidney stones larger than 2 cm and Grade 2 or higher hydronephrosis who underwent ultrasound-guided supine percutaneous nephrolithotomy without ureteral catheterization and fluoroscopy between January 2022 and November 2024. The data of these patients were compared using matched-pair analysis (1:1) with patients who underwent supine percutaneous nephrolithotomy under ultrasound and fluoroscopy guidance with ureteral catheterization (Group 2) in the same period. The groups were compared regarding access time, operation time, stone-free rates, blood loss, and complications. Results: There were no statistically significant differences between the two groups in terms of age, gender, side, stone diameter, stone volume, stone density, hydronephrosis grade and Guy's stone score. Access time was significantly shorter in Group 1 (11.3 ± 3.9 minutes vs. 13.9 ± 4.7 minutes, respectively, 95% CI: 0.3-4.9, p = .026). The mean operation time was 64.4 ± 19.4 in Group 1 and 102.3 ± 31.2 in Group 2, and this difference was statistically significant (95% CI: 24.2-51.6, p = .001). There was no significant difference between the two groups in terms of postoperative 1st month stone-free rates (83.3% vs 86.6%, respectively, p = .723 Conclusion: Compared with standard supine mini percutaneous nephrolithotomy, totally ultrasound guided supine mini percutaneous nephrolithotomy without ureteral catheter is an effective, safe and feasible surgery.